Letter (copy) : Spain - Citrine, Walter, 1887-1983
011-0083-001 WMC/FEM/MT/945 PERSONAL. Secretary's 7th June, 1937. Mr. G. Stolz, International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS, VIIe. Dear Mr. Stolz, SPAIN. Thank you for your letters of the 2nd and 5th June, and for forwarding to me the telegram which you received from Spain via "Le Peuple". If a written communication is received direct from the signatories of the telegram, then I consider it should simply be acknowledged and placed before the next meeting of the Executive Committee. Yours sincerely, General Secretary. 292/946/11/83